PENGENDALIAN HAMA ULAT MENGGUNAKAN LARUTAN DAUN PEPAYA DALAM PENINGKATAN PRODUKSI SAWI (Brassica juncea L.) - Laila Fajri; Tuti Heiriyani; Hilda Susanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
This research was conducted from March to May 2016 at Bina Putra Garden, Guntung Payung, Landasan UlinDistrict, Banjarbaru.  The Purpose of study to determine the effect of papaya leaf solution and the better concentration to against leaf-eating caterpillars pests and to promoted mustard production. The experimental design used a randomized block design one way with four of solution of papaya leaf percentage treatments (0, 40, 70 and 100).  All treatments were made in the formulation 100 ml of solution. Study results showed that papaya leaf solution concentration of 100% is capable to control leaf- eating caterpillar pets and production of mustard.